PENINGKATAN PERAN BIDAN DALAM UPAYA KESEHATAN MASYARAKAT (UKM) PELAYANAN KIA–KB DI PUSKESMAS JUMO KABUPATEN TEMANGGUNG - Susilarini, Susilarini; Widiastuti, Nur (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The aims of the study were to find out the causes of the role of midwives in Community Health Efforts (UKM) for MCH-KB services at the Jumo Health Center, Temanggung Regency, which still needs to be improved, and to formulate efforts to increase the role of midwives in Community Health Efforts (UKM) for KIA-KB services at Jumo Health Center, Temanggung Regency. The research design used was qualitative research, descriptive supported by data obtained by means of observation, interviews and involvement with the research object. The qualitative analysis model uses the Miles & Hubberman model. The results of the study show that the reasons for the increased role of midwives in Community Health Efforts (UKM) for KIA-KB services at the Jumo Health Center in Temanggung Regency still need to be improved, including the competence of midwives who need to be improved and the lack of guidance from the health office, community involvement which is the mainstay of providing first level health services has not been optimally developed and limited budget and infrastructure in carrying out its role in UKM activities of KIA-KB services. Efforts to increase the role of midwives in Community Health Efforts (UKM) for KIA-KB Services at the Jumo Health Center, Temanggung Regency are (a) Increasing the competence of midwives, especially regarding Community Health Efforts (UKM) for KIA-KB services and increasing guidance from the Temanggung District Health Office; (b) Increase the involvement of the community which is the mainstay of the implementation of first level health services; (c) Increasing the budget and infrastructure in carrying out its role in UKM activities for KIA-KB services.